Development of Religious Activities Through Cultural Transformation in Hindu-Muslim Multicultural Educational Institutions - Muhammad Ghafar (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
Plurality is an undeniable fact in Indonesia. This plurality can have good and bad impacts, such as social disunity or social capital for nation-building. The natural source of this dispute cannot be separated from the domination of values and partial truth claims by each group, although various practical interests serve as catalysts. The purpose of this study was to analyze and provide an interpretation of the development of students' religious activities through the transformation of school culture in multicultural educational institutions at Tengger Children's Nature School, Pasuruan. The research method used is qualitative with the type of case study research. Data collection by in-depth interviews, participant observation, and documentation. Data analysis by presenting data, condensing data, and drawing conclusions. As for checking the validity of the data, researchers do this using credibility, transferability, dependability, and confirmability. This research resulted in the finding that the development of a culture of mutual collaboration within the Hindu Muslim community at Tengger Children's Nature School was carried out through activities that prioritized politeness in interactions, besides that all school members were involved in cohesive activities through the school community association, also through organizational activities in traditional event committees. This is a superior value possessed by multicultural educational institutions in the cultural transformation to develop the quality of education, especially in the religious field, where mutual respect can be achieved.